EXPERIMENTAL ANALYSIS OF PRE-TREATMENT OF NATURAL FIBRES - Venkatachalam; Jose, M Sinjo; M.D, K Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
In recent days great attention is given to natural fibres as reinforcement for polymer. Natural fibres compared to glass possess better mechanical properties such as stiffness, flexibility, impact resistance and young’s modulus when compared with glass fibre and eco-friendly. This made it to an attractive material for reinforcement in automobile industry. A lot of research is going on the field of natural fibre which can be used as green material for manufacturing in large scale. .The goal of the work is to produce bumper which cost less compared with long reinforced thermoplastics in which three materials such as coconut husk fibre, coconut spathe and coconut coir are studied .The mechanical properties of the fibre are based on length of the fibre, Absorption and fibre content. Various tests have been conducted on the above materials where the result indicate that coconut husk fibre possess better mechanical properties than other fibres and more advantages than other fibre ,the material possess good impact strength to absorb impact load and increase the protection to front component of the vehicle. The use of composite material can reduce the cost about 50% and increases the factor of safety about 60%.